The Ideological Dynamics of Pan-Islamism and Its Political Impact on Transnational Movements in the Contemporary Muslim World - Saleh Hassan; Abubakar, Fatima; Sherif, Ikilima Abubakar (Pascasarjana IAIN Metro, 2025)
Abstract Pan-Islamism is a movement that emerged as a response to European imperial annexation of Muslim territories and the decline of the Ottoman Empire, driven by a desire to restore unity, morals, and political legitimacy of the Muslim territories. Its transnational orientation has evolved and motivated ideologically diverse movements across the world, ranging from the politically reformist Egyptian Muslim Brotherhood to radical groups like Boko Haram in Nigeria and non-political Jama’at Tabligh. Few studies have examined how Islamist ideologies have shape the trajectories, tactics, and recruitment mechanisms of Pan-Islamism in the contemporary era of digital advancement and geopolitical shifts. Utilizing a constructivist political theory and informed by Islamic political morality as a normative framework, this study adopts a comparative discourse analysis to investigate situations from Nigeria, Egypt, and others. Findings of the study reveal that state responses have shaped the prospects of political Islamist struggles, and ideological volatility often exacerbates the trends of radicalization. The study recommends that the government should logically distinguish between peaceful and extreme Islamists through constructive engagement to avert further radicalization of moderate groups.